(untitled) (Indian Journal of Arid Horticulture, 2025)
Dehydrated tender green pods of khejri (Prosopis cineraria) are utilized as premium vegetable in north-west part of country. Looking into the economic importance of khejri pods (sangri), an experiment was conducted to investigate the effect of pod harvesting stage on drying, rehydration and sensory properties of dried pods during year 2021-22. The maximum dry product recovery (28.22%) was recorded in 13 days maturity closely followed by 16 days (28.08%) maturity pods. Significantly high rehydration capacity was noticed in early harvest (10, 13 and 16 day’s maturity) pods as compared to late harvest (19, 22 and 25 maturity) pods. Desirable sensory properties were also observed in10 to 16 days maturity pods. Based on study, it is concluded that khejri variety Thar Shobha pods should be harvested in 2-3 pickings between 10-16 days after fruiting for getting good quality dried product.